The aesthetic of ruins in Dunhuang murals - Runhong, Liu; Ahmed Fauzi, Tetriana; Suhaimi, Safia Najwa; Mohd Rozlan, Rosyida (Universiti Teknologi MARA, Perak, 2025)
The Mogao Caves in Dunhuang are the world's largest and richest extant Buddhist art site, with relics from thousands of years of overlapping and merging civilizations. Dunhuang murals are a fading, disappearing work of art. This paper analyzes the aesthetic characteristics of Dunhuang murals from four aspects: composition, style, lines, and colors. The reasons for the formation of the Dunhuang mural texture are analyzed through the mottled outlines and faded traces on Dunhuang murals. The erosion of this ancient artwork by nature and humans has produced a delicate beauty similar to the beauty of ruins. This special aesthetic quality has been discussed by Ginsberg (2004), that is, gradual erosion produces new unity and artistic form. The passage of time has endowed Dunhuang murals with three characteristics: the beauty of traces, the beauty of harmony, and the beauty of mistiness. These qualities are also symbols and metaphors for the state of impermanence. The author explores the aesthetic qualities of the texture of Dunhuang murals, especially the peeling and discoloration. The aesthetic of ruins in Dunhuang murals is not merely a historical or cultural phenomenon; it also holds profound implications for contemporary art and philosophy. The concept of ruin aesthetics transcends the boundaries of time and space, offering a unique perspective on the interplay between creation and decay, permanence and impermanence.